Junior's home cooking : over 100 recipes for classic comfort food / Alan Rosen; Beth Allen - Rosen, Alan
Collects recipes from the New York restaurant, including planked salmon caesar salad, New York cheese steak, oven-braised short ribs, chestnut stuffing, and the establishment's famous cheesecake.